2012
DOI: 10.2169/internalmedicine.51.7173
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Group A with Coronary Artery Disease in Young Adults in Taiwan

Abstract: Objective We aimed to investigate the association between the ABO blood groups and the risk of coronary artery disease (CAD) and myocardial infartion (MI) in a young Taiwanese population. Methods We retrospectively recruited 277 consecutive subjects (men younger than 45 years and women younger than 55 years) who underwent coronary angiography (136 with documented CAD and 129 without CAD) at our center, between 2005 and 2008. Their ABO blood groups were determined using standard agglutination techniques. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 33 publications
0
29
5
1
Order By: Relevance
“…In addition, Framingham study revealed a higher incidence of ischemic heart disease in phenotype A (34). Similarly, Lee et al (35) suggest that blood group A is an independent risk factor for coronary artery disease and myocardial infarction in Taiwanese men younger than 45 years and women younger than 55 years. He et al (36) found that blood group B was an independent risk factor for myocardial infarction.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, Framingham study revealed a higher incidence of ischemic heart disease in phenotype A (34). Similarly, Lee et al (35) suggest that blood group A is an independent risk factor for coronary artery disease and myocardial infarction in Taiwanese men younger than 45 years and women younger than 55 years. He et al (36) found that blood group B was an independent risk factor for myocardial infarction.…”
Section: Discussionmentioning
confidence: 89%
“…Considerable evidence underpins CVDs to be linked with ABO blood group system [3,4,23,45] although the mechanism linking ABO blood group with CVD, particularly atherosclerosis, remains unclear. However, previous studies suggest that ABH antigen act as the principal agent for endothelial cell proliferation [3], as such plays a role in the disease process by a modulation in the vascular endothelial haemostasis [1,30]. Besides, the theory that glycosyltransferases (enzymes involved in the modification of the A, B and H antigens) regulate circulation of soluble products of cellular adhesion molecules (CAMs)biomarkers of inflammation-related diseasesmay explain the relationship [4,31].…”
Section: Introductionmentioning
confidence: 99%
“…An association was found between blood type A and SCF. Recently, several studies examined the relationship between ABO blood types and coronary artery disease, and showed that non-A blood groups were associated with CAD (12,13). The present study is the first study to examine the association between SCF and ABO blood types.…”
Section: Discussionmentioning
confidence: 61%